«The Undeniable Inner Compass»: Fyodor Dostoevsky’s «Crime and Punishment» in Light of Mohammad Taghi Jafari’s Concept of Conscience - Hanif, Mohsen; Shoja, Ayda (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
Though originated from a different historio-geographical background, Mohammad Taghi Jafari’s definition of moral conscience in his book The Conscience helps to further explore Fyodor Dostoevsky’s thematic concern with the same notion in Crime and Punishment. The following study probes into the concepts of self-evaluation and repentance as reflected in the novel. It then explores the manifestation of a phenomenon called the «ugliness of conscience» and all its implications ranging from hallucinations and self-hatred to paranoia and nightmares in this classic work of fiction. Moreover, this paper also studies Dostoevsky’s narrative for any sign of emphasis on the priority of «moral conscience»over «intelligence» and «individuaity», as it is also philosophically proposed and stressed by Jafari.
Keywords: Mohammad Taghi Jafari; Fyodor Dostoevsky; Crime and Punishment; moral conscience